1996
DOI: 10.1111/j.1476-5381.1996.tb15304.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the 5‐HT2B receptor agonist, BW 723C86, on three rat models of anxiety

Abstract: 1 BW 723C86 (3 and 10 mg kg-', s.c. 30 min pretest), a 5-HT2B receptor agonist, increased total interaction, but not locomotion in a rat social interaction test, a profile consistent with anxiolysis. 2 The effect of BW 723C86 in the social interaction test is likely to be 5-HT2B receptor-mediated as it was prevented by pretreatment with the 5-HT2C,2B receptor antagonist, SB 200646A, (1 and 2 mg kg-', p.o., 1 h pretest) which did not affect basal levels of social interaction at the doses used. 3 An anxiolytic-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 26 publications
2
51
0
Order By: Relevance
“…According with the results previously obtained by Cheng and Shibata [17] in the hindquarters of old SHR, our experiments showed a higher increased responsiveness for the highest doses tested compared with the vasoconstrictions induced by the same doses in Wistar rats [13]. The absence of vasoconstrictor activity due to the new selective 5-HT 2B agonist BW 723C86 (pE 50 value 7.9) [28], at all the doses used together with the vasoconstriction produced by intra-arterial administration of the 5-HT 2C receptor agonist m-CPP (pE 50 values of 7.4 and 6.9 for 5-HT 2B and 5-HT 2C receptors, respectively [27]), allow us to rule out the possible participation of 5-HT 2B receptors in the vasoconstrictor action. These results are in accordance with the recognized endothelial localization of this receptor subtype, and the vasorelaxation but not vasoconstriction mediated via nitric oxide release [30].…”
Section: Discussionsupporting
confidence: 72%
“…According with the results previously obtained by Cheng and Shibata [17] in the hindquarters of old SHR, our experiments showed a higher increased responsiveness for the highest doses tested compared with the vasoconstrictions induced by the same doses in Wistar rats [13]. The absence of vasoconstrictor activity due to the new selective 5-HT 2B agonist BW 723C86 (pE 50 value 7.9) [28], at all the doses used together with the vasoconstriction produced by intra-arterial administration of the 5-HT 2C receptor agonist m-CPP (pE 50 values of 7.4 and 6.9 for 5-HT 2B and 5-HT 2C receptors, respectively [27]), allow us to rule out the possible participation of 5-HT 2B receptors in the vasoconstrictor action. These results are in accordance with the recognized endothelial localization of this receptor subtype, and the vasorelaxation but not vasoconstriction mediated via nitric oxide release [30].…”
Section: Discussionsupporting
confidence: 72%
“…However, the 5-HT 2B receptor is located principally in the periphery and only sparsely in the central nervous system in rats (Pompeiano et al, 1994). In addition, although it has been reported that a selective 5-HT 2B receptor agonist exhibited anxiolytic effects in rodents, a selective 5-HT 2B receptor antagonist was without effect (Kennett et al, 1996(Kennett et al, , 1998. Last, anxiolytic activity of a mixed 5-HT 2C/2B receptor antagonist has been ascribed to activity at the 5-HT 2C but not 5-HT 2B receptor (Bromidge et al, 2000).…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, the selective 5-HT 2B receptor antagonist, SB204,741 (Cussac et al 2002), showed no substitution to mirtazapine at doses active in other behavioral procedures like modulation of sleep architecture (Kantor et al 2004). In addition, though 5-HT 2B receptor blockade reduces the locomotor actions of 3,4-methylenedioxymethamphetamine (ecstasy; MDMA; Doly et al 2008), and 5-HT 2B receptor stimulation is associated with anxiolytic properties (Kennett et al 1996), there is no evidence that antagonism of central 5-HT 2B receptors greatly affects mood. A role of 5-HT 2A receptor blockade in the DS properties of mirtazapine also appears unlikely inasmuch as SB242,084, SB243,213, and S32006 all possess low affinity for 5-HT 2A receptors, and the highly selective antagonist at 5-HT 2A receptors, MDL100,907 and SR46349-B, failed to significantly substitute for mirtazapine.…”
Section: Discussionmentioning
confidence: 99%